3D Ordered Macroporous: A Novel 3DOM TiO2 Based Multifunctional Photocatalytic and Catalytic Platform for Energy Regeneration and Pollutants Degradation (Adv. Mater. Interfaces 4/2021). Issue 4 (19th February 2021) - Ding, Yang; Huang, Lina; Barakat, Tarek; Su, Bao‐Lian
Abstract : The ternary three‐dimensional ordered macroporous (3DOM) heterojuncted nanocomposites (3DOM‐Pt/Bi2 MoO6 /TiO2 ) are designed as high performance multifunctional platform for photocatalytic dye degradation, photoelectrocatalytic water splitting and thermal‐catalytic toluene decomposition owing to the intimate heterostructure, the fast mass transfer and the improved separation of photogenerated carriers. This work opens new avenue in developing multifunctional platforms for versatile applications in photocatalytic, photoelectrochemical and catalytic fields. More details can be found in article number 2001879 by Bao‐Lian Su and co‐workers.